Modern and contemporary political theater from the Levant a critical anthology - Myers, Robert (Professor of English) (Brill, 2019)
"In Modern and Contemporary Political Theater from the Levant, A Critical Anthology, Robert Myers and Nada Saab provide a sense of the variety and complexity of political theater produced in and around the Levant from the 1960s to the present within a context of wider discussions about political theater and the histories and forms of performance from the Islamic and Arab worlds. Five major playwrights are studied, Īsam Mahfuz, from Lebanon; Muhammad al-Maghut and Sād Allah Wannus, from Syria; Jawad al-Asadi, from Iraq, Syria and Lebanon; and Rāida Taha, from Palestine. The volume includes translations of their plays The Dictator, The Jester, The Rape, Baghdadi Bath and Where Would I Find Someone Like You, Āli?, respectively"--
Keywords: Geschichte 1960-; Politisches Theater; Arabische Staaten; Political plays, Arabic / Middle East / History and criticism; Political plays, Arabic / Middle East / Translations into English; Political plays, Arabic; Middle East; Criticism, interpretation, etc; Translations; Anthologie